Kualitas Relasi Remaja dan Orang Tua dengan Kecanduan Internet pada Siswa Sekolah Menengah Atas Pengguna Smartphone - Soffa Mar'ah Azizah; Tri Rejeki Andayani; Berliana Widi Scarvanovi (Jurnal Psikologi Teori dan Terapan, 2019)
Smartphone is the most widely used device to access internet. Adolescents tend to access internet excessively that makes them to be more dependent and addicted to it. Internet addiction can be influenced by both internal and external factors and one of them is the quality of parent-adolescent relation. The purpose of this study is to examine the correlation between the quality of parent-adolescent relationship and internet addiction. Population of this study was high school students in Surakarta who use smartphones. The total number of 354 subjects was recruited using multistage cluster random sampling by determining the selected classrooms from the selected clusters. The instruments used to collect data were Internet Addiction Scale (Î± = 0,860), Quality of Father-Adolescent Relationship Scale (Î± = 0,815), and Quality of Mother-Adolescent Relationship Scale (Î± = 0,815). Data were analyzed using multiple linear regression. The result shows that there is a significant negative correlation between quality of parent-adolescent relationship and internet addiction with Fcalculated > Ftable (8,174 > 3,03) and r = -0,211 in the significant value of  p <0,05. Partially, the significancy of correlation between quality of relationship and internet addiction is only proved for mother-adolescent relationship.Keywords: Internet addiction, internet user, parent-adolescent relationship